Opening sequences, the entrance hall on television fiction: identity building and brand - Magro-Vela, Silvia (2020)
Opening sequences has been suffered from a transformation process until becoming an integral and integrating part of fictional story. The present text collects a study of the opening of Isabel, Víctor Ros and El Ministerio del tiempo, created by Javier Olivares. A research developed from four main points of work, analysis of formal, narrative, typographic and sound aspects. Through common and dissimilar traits shared with credit titles, it is about proving the relationship with the building process of identity and brand of the audiovisual product as an independent unit from its creator.